2023
DOI: 10.3390/ma16093551
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalysts for Glycerol Biorefineries: Hydrogenolysis to 1,2-Propylene Glycol

Abstract: Research on the use of biomass resources for the generation of energy and chemical compounds is of great interest worldwide. The development and growth of the biodiesel industry has led to a parallel market for the supply of glycerol, its main by-product. Its wide availability and relatively low cost as a raw material make glycerol a basic component for obtaining various chemical products and allows for the development of a biorefinery around biodiesel plants, through the technological integration of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 304 publications
0
3
0
Order By: Relevance
“…As it can be seen, glycerol conversion decreases as the water concentration increases. This behavior is expected as water is a by-product of the reaction, so its formation shifts the equilibrium towards the reactants [51]. It has been reported that in the presence of Rh 0.02 Cu 0.4 /Mg 5.6 Al 1.98 O 8.57 catalyst, glycerol conversion decreases from 91% to 69% when the water content increases from 0 wt.% to 40 wt.%, using ethanol as a solvent at 180 • C and 2 MPa of H 2 [52].…”
Section: Effect Of the Water Concentrationmentioning
confidence: 89%
See 1 more Smart Citation
“…As it can be seen, glycerol conversion decreases as the water concentration increases. This behavior is expected as water is a by-product of the reaction, so its formation shifts the equilibrium towards the reactants [51]. It has been reported that in the presence of Rh 0.02 Cu 0.4 /Mg 5.6 Al 1.98 O 8.57 catalyst, glycerol conversion decreases from 91% to 69% when the water content increases from 0 wt.% to 40 wt.%, using ethanol as a solvent at 180 • C and 2 MPa of H 2 [52].…”
Section: Effect Of the Water Concentrationmentioning
confidence: 89%
“…the reaction, so its formation shifts the equilibrium towards the reactants [51]. It has be reported that in the presence of Rh0.02Cu0.4/Mg5.6Al1.98O8.57 catalyst, glycerol conversion creases from 91% to 69% when the water content increases from 0 wt.% to 40 wt.%, us ethanol as a solvent at 180 °C and 2 MPa of H2 [52].…”
Section: Kinetic Modelmentioning
confidence: 99%
“…In this context, it has been extensively reported in the literature that glycerol hydrogenolysis allows for the production of bio-propylene glycol (1,2-PG), a product employed in the pharmaceutical, cosmetics, food industries and in the chemical industry in general. At present, 1,2-PG is obtained through a petrochemical process, so the production of 1,2-PG from glycerol is an environmentally friendly alternative, which, in the near future, could allow for decreasing the present dependence on fossil resources as raw materials [3].…”
Section: Introductionmentioning
confidence: 99%